2016 IEEE Aerospace Conference 2016
DOI: 10.1109/aero.2016.7500717
|View full text |Cite
|
Sign up to set email alerts
|

NEEMO 18–20: Analog testing for mitigation of communication latency during human space exploration

Abstract: NASA Extreme Environment Mission O perations (NEEMO) is an underwater spaceflight analog that allows a true mission-like operational environment and uses buoyancy effects and added weight to simulate different gravity levels. Three missions were undertaken from 2014-2015, NEEMO 18-20. All missions were performed at the Florida International University's Aquarius Reef Base, an undersea research habitat. During each mission, the effects of communication latencies on operations concepts, timelines, and tasks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Our study design integrated our ConOps research questions with marine science objectives for the mission. The marinescience objectives included both new reef exploration with the intent to perform targeted sampling of specific marinescience species as well as revisiting of marine-science sites sampled during NEEMO 20 [11]. While performing new reef exploration, timelines were strategically designed to include different amounts of ST assimilation time within and across EVAs.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study design integrated our ConOps research questions with marine science objectives for the mission. The marinescience objectives included both new reef exploration with the intent to perform targeted sampling of specific marinescience species as well as revisiting of marine-science sites sampled during NEEMO 20 [11]. While performing new reef exploration, timelines were strategically designed to include different amounts of ST assimilation time within and across EVAs.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Mars mission ConOps, capabilities, and communication protocols have been tested and iteratively developed during previous analog tests. They include the results and lessons learned from previous analog tests, beginning with NASA's Desert Research and Technology Studies (DRATS, 2010-11) [7,8] and continuing through the Pavilion Lake Research Project (PLRP, 2011-14) [9], NASA Extreme Environment Mission Operations (NEEMO) missions 16-20 (2012-16) [10,11], and BASALT (2015-present) [12].…”
Section: Exploration Traverse Operations Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IV crewmembers may alternate roles in 6-hr shifts between serving as science capsule communicator (CapCom) between an Earth-based science support team and the PEV crew, and performing exercise and general housekeeping activities; both habitat crewmembers may be needed during certain portions of the PEV exploration excursion, including during EVA. Previous analog field studies conducted with communication latency (between Earth and Mars), including the NASA Research and Technology Studies (RATS) and NASA Extreme Environment Mission Operations (NEEMO), have clearly demonstrated the benefit of one or two IV crewmembers supporting EVAs, freeing the PEV crewmembers to focus on piloting and EVA tasks [18] [21]. After the PEV returns from its two-week excursion, all four crewmembers would remain at the habitat for three weeks, thus restarting the nominal exploration pattern.…”
Section: Proposed Mission Operations and Timelinementioning
confidence: 99%
“…issue, engineers focus on how to handle communications in conditions of high latency and also of low bandwidth, those that will be present in the exploration of planets in our solar system (Beaton et al 2017;Chappell et al 2016). They assume this problem and try to optimize non-real time communications in the best conditions possible (Lester and Thronson 2011).…”
mentioning
confidence: 99%